Mental health and well-being interventions in sport research, theory and practice - Breslin, Gavin; Leavey, Gerard 1957- (Abingdon, Oxon New York, NY Routledge, 2019)
Mental Health and Well-being Interventions in Sport provides an indispensable guide for researchers and practitioners wanting to understand and implement sport-based intervention processes. This important book adopts an evidence based approach, discussing the context of the intervention, its design and implementation, and its evaluation and legacy. With cases on depression, eating disorders, and athletic burnout, the book is designed to provide practitioners, policy makers and researchers with a cutting-edge overview of the key issues involved in this burgeoning area, while also including cases on how sport itself has been used as a method to improve mental health. Written for newcomers and established practitioners alike, the text is an essential read for researchers and practitioners in better understanding the sport setting-based intervention processes through presenting current research, theory and practice, applicable in a variety of sports settings and context
Getting started : an overview -- Section 1: Development of mental health awareness programmes for athletes, coaches and parents -- The optimum performance programme in sports : a case of bulimia nervosa in a lean sport athlete -- Prevention of burnout and depression in junior elite swimmers-- Bolstering psychological health using rational emotive behaviour therapy -- The State of Mind Ireland (SOMI) Programme for student athletes -- Ahead of the game : a sports-based mental health program for adolescent males -- Tackling the blues : a sport and education based mental health programme for children and young people -- Section 2: Engaging the wider community in mental health awareness through sport -- Motivating prisoners to exercise : an evaluation of the Cell Workout Workshops -- Reflections on implementing the Active Choices Rugby Programme to enhance mental health and well-being of young men in prison -- Critical reflection and the way forward for mental health in sport
Includes bibliographical references and index
Keywords: Athletes -- Mental health -- Case studies; Exercise -- Psychological aspects -- Case studies; Sports -- Psychological aspects -- Case studies